Toward robust and quantifiable automated IFC quality validation. Issue 3 (August 2015) - Solihin, Wawan; Eastman, Charles; Lee, Yong-Cheol
Highlights We identify quantifiable rules for testing a good quality IFC file. We define classifications of the validation rules including syntax and semantics. We outline initial list of validation rules covering all aspects of IFC testing. The validation rules include well defined rules for geometry and spatial related tests. We propose rules for automated IFC import testing.